2020
DOI: 10.25225/jvb.20033
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the hidden costs of livestock guarding dogs: a case study in Namaqualand, South Africa

Abstract: The use of livestock guarding dogs (LGDs) has been widely advocated as a responsible tool for reducing livestock predation and conserving wildlife. However, their hidden ecological costs have rarely been investigated. We analysed scats (n = 183) from six LGDs and visited Global Positioning System (GPS) location clusters (n = 352) from nine GPS-collared LGDs to reconstruct their diet and assess impacts on wildlife and livestock in Namaqualand, South Africa. Wild mammals, including 10 native species, and small-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…LGDs were sometimes prone to chasing wildlife, additional monitoring as part of the program may include spatial monitoring of LGDs movements and predation risk to wildlife, which has been employed to monitor their effectiveness and impact elsewhere (Bromen et al 2019, Young et al 2019, Drouilly et al 2020.…”
Section: Defensive Responses Bymentioning
confidence: 99%
“…LGDs were sometimes prone to chasing wildlife, additional monitoring as part of the program may include spatial monitoring of LGDs movements and predation risk to wildlife, which has been employed to monitor their effectiveness and impact elsewhere (Bromen et al 2019, Young et al 2019, Drouilly et al 2020.…”
Section: Defensive Responses Bymentioning
confidence: 99%
“…LGDs and wild predators have relied on indirect information such as farmers' memory, reports and anecdotes (Green et al 1984, Marker et al 2005a, b, Potgieter et al 2013, Leijenaar et al 2015, Whitehouse-Tedd et al 2020 or, recently, on the analysis of LGDs diet (Drouilly et al 2020, this special issue).…”
Section: Interactions Between Livestock Guarding Dogs and Wolves In Tmentioning
confidence: 99%
“…The remaining estimates originated from direct researcher observations and farmer reports, so are subject to human error and biases. For example, LGDs might behave differently whilst being observed or accompanied by humans (Drouilly et al 2020) and are often out of sight of farmers, meaning farmer reports may underestimate the occurrence of these behaviours (Whitehouse-Tedd et al 2020). Furthermore, the percentage of LGDs involved does not provide insight into the frequency of the interactions per dog over a defined time period.…”
Section: Interactions Responses and Effectsmentioning
confidence: 99%
“…In addition to the 43 publications reporting LGDs to chase and kill wildlife, we found two publications investigating LGD diet via morphological identification of prey remains in LGD scats. One revealed the consumption of ten wild mammal species by LGDs, as well as small quantities of invertebrates, reptiles and birds (Drouilly et al 2020), and the other reported the rare occurrence of scrub hare (Lepus saxatilis), common duiker (Sylvicapra grimmia) and rodent remains in LGD scats (van Vliet 2011). However, it is not possible to confidently distinguish between remains in the scats that were actively hunted or scavenged by LGDs.…”
Section: Interactions Responses and Effectsmentioning
confidence: 99%